Proposals for Privatization in Eastern Europe - Borensztein, Eduardo (IMF Working Papers; Working Paper ;, 1991)
This paper discusses several proposals for a wholesale privatization of public enterprises in Eastern Europe. These proposals include the distribution of 'vouchers' to private citizens as well as the use of mutual funds, privatization companies and other forms of financial intermediaries. The paper analyzes the implications for economic efficiency of the different forms of ownership and control that would emerge from the proposals as well as their main macroeconomic consequences.